Multi-technical approach to evaluate the impacts caused by the Vazante Mine (MG) on the Santa Catarina River flow loss through the overexploitation of a fissure-karst aquifer and simulation of mitigating solutions by numerical modeling - Ferreira, Otavio Barbosa (2023)
The water loss in rivers and streams is one of the immediate effects of aquifer overexploitation. Particularly in the context of underground mining, notable changes in the natural groundwater flow regime are observed due to the pumping required to keep underground galleries drained. In the northwest region of the Brazilian state of Minas Gerais, in Vazante municipality, the Santa Catarina River (SCR) undergoes a drying up processes related to the Vazante underground mine dewatering. To properly understand this phenomenon, it is necessary to have a broad knowledge about the hydrogeological dynamics of the region, mainly in areas of complex geology with karst features and systems of faults and fractures. This study performed a multi-technical approach to spatialize and characterize the most hydraulically conductive brittle structures and karst conduits responsible for the hydraulic connections between the drying river and the underground mine. The methodology was based on field investigation, structural framework, remote sensing (Differential Interferometry DinSAR), geophysics (electrical resistivity), and fluorescent tracer tests. A transient numerical groundwater flow modeling was carried out to evaluate mitigation solutions for the SCR drying-up problem and predict the impacts that a possible extreme drought event in the region could cause on the river flow loss. The assessment of discontinuities mapped inside the mine identified that the most productive water-bearing brittle structures show a subvertical NW/SE structural trend. Fluorescent dye tracers indicated the existence of hydraulic connections between the SCR and the Vazante underground mine. The DinSAR imagery suggested that the terrain surface movements are being controlled by hydrogeologically conductive structures located in the shallow portion of the aquifer. The electrical resistivity survey revealed low resistivity zones between the SCR to the Vazante mine, indicating the presence of preferential flow-paths. The integrated multi-technical approach allowed classifying the brittle structures according to their potential (high or medium) to control the groundwater flow. The karst conduits that connect the drying river to the underground mine were also spatialized. All simulations (upstream water supply, riverbed-waterproofing, obstruction of sinkholes and extreme drought) showed a trend of increase in the SCR flow loss related to the advance of the underground mine galleries, followed by stabilization over the simulated period (2022-2030). The upstream water supply and sinkholes obstruction scenarios showed the highest and lowest river flow loss (35.1% increase and 47.7% decrease, respectively) and mine pumping rates (7.0% increase and 37,9% decrease, respectively). The riverbed-waterproofing scenario caused the largest expansion in the depression cone (513 m) towards the municipality of Vazante until 2030.